Innovation et compétitivité : de nouvelles politiques industrielles ? - Antoine Grandclément (Bulletin de l’Association de Géographes Français)
This paper wishes to show the emergence of new industrial and innovation policies in France namely the competitiveness clusters policy and the “Investissements d’Avenir”. The focus on the conceptual turn of competitiveness has often lead to ignore geographical issues. The aim is therefore to understand how these policies tranform spatial hierarchies and the strategies of industrial and scientific actors.